HUBUNGAN ANTARA KESEIMBANGAN DINAMIS DENGAN AKTIVITAS SEHARI-HARI PADA PENGGUNA TRANSTIBIAL PROSTHESIS DI IPOED KAKI PALSU - Novita Kurniawati; Syarifah Syarifah; Dody Suprayogi (Rena Cipta Mandiri, 2025)
Transtibial amputation affects balance and the ability to perform daily activities. The use of a transtibial prosthesis can improve mobility, but still has the potential to cause dynamic balance disorders that have an impact on independence. This study aims to determine the relationship between dynamic balance and daily activities in transtibial prosthesis users. This research is an observational analytic study with a cross-sectional approach conducted in January 2025 at the IPOED False Foot Clinic. The study subjects consisted of 12 transtibial prosthesis users selected by purposive sampling from a total population of 31 people, based on the inclusion and exclusion criteria. Data were analyzed using normality test and Spearman Rank correlation test. The results of the analysis showed a p value of 0.207 (p> 0.05), which means that there is no statistically significant relationship between dynamic balance and daily activities in transtibial prosthesis users. The correlation coefficient value of -0.392 indicates a moderately negative relationship. This means that an improvement in balance is not always accompanied by an increase in daily activities, but this relationship is not statistically significant. The results showed no significant relationship between dynamic balance and daily activities in transtibial prosthesis users. This finding can be the basis for further research and consideration in developing a more targeted rehabilitation program.